The impact of primary care supported shielding on the risk of mortality in people vulnerable to COVID-19: English sentinel network matched cohort study - Zarif, A; Joy, M; Sherlock, J; Sheppard, JP; Byford, R; Akinyemi, O; Bankhead, CR; Deeks, A; Ferreira, F; Jones, N; Liyanage, H; McGagh, D; et al. (Elsevier, 2021)
Objectives To mitigate risk of mortality from coronavirus 2019 infection (COVID-19), the UK government recommended ‘shielding’ of vulnerable people through self-isolation for 12 weeks.